Pemberdayaan Perempuan dalam Pengembangan UMKM: Studi Kasus Produk Lokal “Mie Des” di Dusun Klisat Kalurahan Srihardono Kecamatan Pun dong Kabupaten Bantul - Uskha Dyah Arsanti (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to describe the form of women's empowerment in the development of Micro, Small, and Medium Enterprises (MSMEs) through a case study of the local product business "Mie Des" in Klisat Hamlet, Srihardono Village, Pundong District, Bantul Regency. The method used is descriptive qualitative research with a case study approach, where data is collected through observation, interviews, and documentation of business actors and community leaders. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results show that women's empowerment in the "Mie Des" business includes five main indicators, namely Opportunities, Support, Strengthening, Protection, and Supervision. Women have an important role in the production, management, and marketing of "Mie Des" products, and demonstrate increasing economic independence. Support from family and community is a significant supporting factor, although access to assistance with production tools is still uneven. In terms of empowerment, business actors acquire new skills and become more confident in making decisions. However, legal protection for women's MSMEs is still minimal, and external supervision has not been carried out continuously.